2019
DOI: 10.2147/copd.s194367
|View full text |Cite
|
Sign up to set email alerts
|

<p>Exacerbations and health care resource use among patients with COPD in relation to blood eosinophil counts</p>

Abstract: PurposeCurrent understanding of the relationship between COPD phenotype and health care resource utilization (HCRU) is limited. This real-world study evaluated disease burden and HCRU for COPD subgroups prone to exacerbation as defined by blood eosinophil (EOS) count and multiple inhaler triple therapy (MITT) use.MethodsThis was a large-scale, retrospective, longitudinal, observational cohort study using data from the US IBM Watson Explorys real-world database (GSK Study HO-17-18395). The population of interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…12 In another recent study based on EMR data linked to claims with a large sample size across many care settings in the United States, Mullerova et al found that blood eosinophil counts ≥150 cells/µL were associated with increased HCRU and higher exacerbation rates compared with blood eosinophil counts <150 cells/μL. 13 The current study has several strengths. Our study was based on a large population of COPD patients identified from a single ambulatory EMR system in use in all 50 states and includes linkage to a large transactional claims database that captures a large percentage of the prescription, medical, and hospital claims in the United States.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…12 In another recent study based on EMR data linked to claims with a large sample size across many care settings in the United States, Mullerova et al found that blood eosinophil counts ≥150 cells/µL were associated with increased HCRU and higher exacerbation rates compared with blood eosinophil counts <150 cells/μL. 13 The current study has several strengths. Our study was based on a large population of COPD patients identified from a single ambulatory EMR system in use in all 50 states and includes linkage to a large transactional claims database that captures a large percentage of the prescription, medical, and hospital claims in the United States.…”
Section: Discussionmentioning
confidence: 75%
“…11 Two recent US studies on patients with COPD have also found an increase in healthcare resource utilization with increasing eosinophil count. 12,13 This retrospective, observational database study of COPD patients spanning multiple real-world US practice settings is the first comprehensive evaluation of the association of blood eosinophil counts with health care utilization and cost outcomes reflecting current clinical practice across the US. The aims of this cohort study were to describe patient characteristics, health care utilization and cost across groups with increasing blood eosinophil counts in a broadly representative COPD patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated a substantial annual burden associated with eosinophilic COPD ( 29 , 30 ). In a cross-sectional study of 2,832 patients in the US, subjects with elevated eosinophil counts had numerically higher all-cause and COPD-related health care resource utilization (HCRU) and cost each year ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, number of COPD‐related in‐patient days within severe COPD patients and overall mortality for all COPD patients were greater in noneosinophilic COPD patients in the study from Finland 37 . However, there are some studies indicating an association between elevated blood eosinophil count and exacerbations 38,39 . Vedel‐Krogh et al calculated a 1.76‐fold increased risk of severe exacerbation related with high blood eosinophil counts 18 .…”
Section: Discussionmentioning
confidence: 87%
“… 37 However, there are some studies indicating an association between elevated blood eosinophil count and exacerbations. 38 , 39 Vedel‐Krogh et al calculated a 1.76‐fold increased risk of severe exacerbation related with high blood eosinophil counts. 18 Kerkhof et al found an elevated risk exacerbation related with eosinophils but only in ex‐smoker COPD population.…”
Section: Discussionmentioning
confidence: 99%